The readiness and acceptance of multimedia technology in teaching English Lesson Year 1: a survey / Julia Aida Abd Salam - Abd Salam, Julia Aida (2005)
This research is about the survey of the readiness and acceptance of multimedia technology in teaching English Lesson Year 1. Most of the teachers only use text book and pictures to teach English. Bringing the technology to the classroom requires the preparation of facilities and the readiness of everybody to accept it. The aims of this research are to identify the readiness of using multimedia technology for teaching English in primary school and to investigate their level of acceptance towards this new way of education. The research began by distributing questionnaires to the Year 1 English teachers in primary schools located in Shah Alam. The primary schools were selected randomly and there were 30 respondents answered the questionnaires. The survey shows that there were 73.33% of the respondents knew about computer and able to operate it. They were familiar about the functions and knew how to use them. There were 73.33% of the teachers referred to computer software in order to help them to teach English. Majority of the respondents agreed to accept the multimedia technology for teaching based on their motivation. It indicated that 50% of the respondents had moderate acceptance level while another 50% stated that they were strongly agree to accept the technology and had high level of acceptance. It is also found out that the respondents who had a high acceptance level were those who referred to other software to help them in teaching English language, had attended computer courses before and also those who had their own computer. It is concluded that the teachers were ready to accept the multimedia application for teaching English. It is recommended that the content of the multimedia product for teaching English soon must be suitable for young children, must follow the syllabus, colorful, attractive and easy to navigate.